Efficiency of Rice Husk Ash as Cementitious Material in High-Strength Cement-Admixed Clay - Pornkasem Jongpradist; Watee Homtragoon; Raksiri Sukkarak; Warat Kongkitkul; Pitthaya Jamsawang (Advances in Civil Engineering)
The potential and efficiency of using rice husk ash (RHA) to add up or partially replace Portland cement in deep cement mixing technique are examined. A series of unconfined compression tests on cement-RHA-stabilized clay are conducted to investigate the influence of RHA on the mixture properties. Special attention is paid to its efficiency for increasing the strength by partial cement replacement to obtain high-strength soil cement, and it is compared with fly ash. Test results indicate that up to 35% of RHA could be advantageously added up to enhance the strength if the cement content in the mixture is larger than 10%. The RHA enhances the strength of cement-admixed clay by larger than 100% at 28 days. For curing time of 14 and 28 days, the RHA exhibits higher efficiency on Portland cement replacement when the cement and overall cementitious contents are not less than 20 and 35%, respectively. The optimum condition for high-strength mixture is achieved when RHA is added to the 20% cement content mixture. When compared with fly ash of similar grain size, the efficiency of RHA is higher when the content to be added is greater than 15%. This indicates the suitability of RHA for use in high-strength soil-cement.